An econometric analysis of the current account deficit in Turkish Economy - Terzi, Nuray; Sarıdoğan, Ercan (İktisadi ve İdari Bilimler Dergisi, 2007)
The world economy maintained its high rated growth in 2006. While China continued to become the main determinant of the ongoing strong growth tendency of the world economy, stable growth in the economies of the European Union and Japan contributed to the growth in the world economy. Uncertainties about oil prices and international liquidity conditions and global in stabilities, such as current account deficits are the lea ding risks for growth of the world economy. Current account deficits have been seen developed and developing countries. IMF estimates that curr ent account deficits will continue in U.S and in some emerging countries. In Turkey, current account deficit exceeded 8 percent of GDP in 2006, as well. The main goal of this paper is to provide general framework about current account balance and analyze the dynamics of current account deficit in Turkey by using time series econometric techniques.
Keywords: Current Account Deficit, Turkish Economy, Granger Causality.